2018
DOI: 10.11114/jets.v6i11a.3805
|View full text |Cite
|
Sign up to set email alerts
|

Perception- Attention - Memory Reaction Time of PE Teacher and Computer Teacher Candidates

Abstract: The purpose of the study is to determine the visual and auditory reaction time, perception, attention and memory levels of PE teacher candidates and computer teacher candidates.For this purpose, after giving necessary information to the teacher candidates of the Department of Physical Education and Sports and the candidates of Computer Teaching Department of Kocaeli University, 88 voluntary students, were applied Benton Perception, Attention-Memory test and Newtest 1000 which determined their visual and audito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Our object 144 partici height, bod 21.89 ± 4.5 Karagün (2018) examined the MR performances of students studying computer and physical education teaching, he found a statistically significant difference in favor of students studying computer teaching. Jansen et al (2009) found that there was an increase in MR performance of sedentaries exercising at least 3 days a week for 45 minutes per day.…”
Section: Resultsmentioning
confidence: 84%
“…Our object 144 partici height, bod 21.89 ± 4.5 Karagün (2018) examined the MR performances of students studying computer and physical education teaching, he found a statistically significant difference in favor of students studying computer teaching. Jansen et al (2009) found that there was an increase in MR performance of sedentaries exercising at least 3 days a week for 45 minutes per day.…”
Section: Resultsmentioning
confidence: 84%